EVALUASI PENERAPAN APLIKASI ELSIMIL DALAM MENGATASI RISIKO STUNTING PADA KADER TPK DI KELURAHAN KEPANJEN MALANG - Dita Ayu Amelia Anggraeni; Wandi Wandi; Jupriyono Jupriyono (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
The National Population and Family Planning Agency has developed a new application called the Electronic Application Ready for Marriage & Ready for Pregnancy to help reduce stunting in Indonesia. The app is aimed at prospective brides, toddlers, Fertile Age Couples, Pregnant Women, and Postpartum Mothers as a screening tool to detect risk factors for stunting. Running the ELSIMIL application requires assistance from Family Assistance Team cadres to screen targets. The purpose of this study was to determine the application of the ELSIMIL application in overcoming the risk of stunting in TPK cadres in Kepanjen Village, Malang Regency. This study used qualitative methods and a case study design to examine the effectiveness of ELSIMIL, a data screening and filling tool, used by TPK cadres. Data collection techniques used interviews, observation, and documentation using domain analysis. The results show that ELSIMIL is effectively used by TPK cadres for screening and filling in target data. ELSIMIL is efficient to use with fast screening results through easy to use functions and features. The ELSIMIL application can be accessed equally by all TPK cadres but there are still many obstacles both personal and from the system. ELSIMIL is responsive displaying the functions of the application features without interruption when responding to TPK cadres when entering sasa ran data. ELSIMIL is precise displaying no interference generated from outside the system and is safe for TPK cadres. Evaluation of the implementation ELSIMIL application will have an impact on reducing stunting rates in Indonesia.